Agência-contexto no engravidar de mulheres adolescentes - Silva, Ana Maria Nunes da (2020)
This is a report of a qualitative research that analyzed the perspective of low-income adolescent women in the face of pregnancy, giving visibility to the intertwined context involved in this event. After being approved by the Ethics Committee (Opinion no 3.228.348), we performed this work in six Family Health Units, in a neighborhood of lower socioeconomic status in the southern region of Cuiabá, Mato Grosso. We analyzed the speeches of 16 pregnant women who “intended” the pregnancy, aged between 15 and 19 years old, undergoing prenatal care at one of the chosen health units. In-depth interviews were conducted with the support of additional resources (self-portrait, relational map and photo-elicitation). The analysis was based on general precepts of Content Analysis, of the thematic type, and on the adopted theoretical perspective. We found the centrality of motherhood and the constitution of a family in their own essence in the lives of the participants. Both elements were linked to the incorporation of the ideal of motherhood and the nuclear family construction of modern discourse, the restricted conditions of life and the experienced psychoactive needs. In the latter sense, they sought to find a meaning in their lives, positive relationships of affection, overcoming suffering, as well as having protection and a happy life. In the constitution of the family itself, the family models experienced proved to be prominent, as well as the support received from the nuclei of origin and/or the partners. It showed to be particularly important, for pregnancy, to feel loved, well looked after and to have confidence in the partner, his company and habitual protection, besides life and reproductive goals in common. The fact that they did not see themselves as adolescents and think they were ready for the “life of responsibility” that they understood that motherhood required also contributed to their decisions. Consistent with the prioritized projects, their relational and affective-sexual trajectories were characterized by the experience of several events (courtship, cohabitation/marriage, pregnancy) in a short intercourse and by the adoption of contraceptive methods as an adjunct to those events. In the perspective of their sexual and reproductive lives, these aspects, especially pregnancy, were not part of a matured process and shared by and between them and their partners, commonly starting from these women the initiatives, pressures and decisions. In this sense, there was a marked influence of the experience of fanciful thoughts related to those events, interspersed with matured thoughts, thereby constituting their developmental processes. We can conclude that there are several prospective, developmental, family and social aspects intertwined in the different dimensions of the life of the “adolescents” implied in their pregnancies. The promotion of care for reproductive planning, such as the prevention or the support for pregnancy/motherhood, particularly for women using public health services, requires consideration of the complexity involved in this process.